2010
DOI: 10.1073/pnas.0914960107
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of PEX1-Gly843Asp peroxisome dysfunction by small-molecule compounds

Abstract: Zellweger spectrum disorder (ZSD) is a heterogeneous group of diseases with high morbidity and mortality caused by failure to assemble normal peroxisomes. There is no therapy for ZSD, but management is supportive. Nevertheless, one-half of the patients have a phenotype milder than classic Zellweger syndrome and exhibit a progressive disease course. Thus, patients would benefit if therapies became available and were instituted early. Recent reports indicate several interventions that result in partial peroxisom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 44 publications
1
72
1
Order By: Relevance
“…The PEX1 protein is normally involved in peroxisomal import. It was shown that betaine improved peroxisomal import of various proteins in fibroblasts exhibiting mutant PEX1 protein with G843D substitution36. The G843D PEX1 substitution is associated with a mild form of the disease, and its function can be partially rescued by expression of its binding partner PEX6, indicating that a conformational rescue takes place, similarly to what we here observed upon coexpression of T122K and AGU-Fin with the wildtype AGA.…”
Section: Discussionsupporting
confidence: 85%
“…The PEX1 protein is normally involved in peroxisomal import. It was shown that betaine improved peroxisomal import of various proteins in fibroblasts exhibiting mutant PEX1 protein with G843D substitution36. The G843D PEX1 substitution is associated with a mild form of the disease, and its function can be partially rescued by expression of its binding partner PEX6, indicating that a conformational rescue takes place, similarly to what we here observed upon coexpression of T122K and AGU-Fin with the wildtype AGA.…”
Section: Discussionsupporting
confidence: 85%
“…Sofar, only in rats the in vivo effect of this drug on hepatic peroxisomal parameters have been investigated [152]. For PBD due to misfolded proteins, drugs belonging to the class of chaperones, are promising agents to restore peroxin function, as shown in fibroblasts [153]. To overrule premature stop mutations nonsense suppressor therapies have been tested in fibroblasts [154].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Patients with an infantile Refsum phenotype may survive through adolescence and manifest moderate-to-severe mental retardation, hypotonia, progressive retinopathy and sensorineural deafness and may not always have dysmorphic facies. The PEX1 p.Gly843Asp allele encodes a peroxin with residual protein function 8 9. The presence of at least one p.G843D allele predicts a phenotype milder than Zellweger syndrome 10.…”
Section: Communicationmentioning
confidence: 99%